Family ties, do they matter? family ownership and firm performance in Peru. (2012)
This paper studies the relationship between ownership concentration, family ownership, management, and market and accounting performance for 59 industrial firms listed in the Lima Stock Exchange during the period of 1999 to 2005. An inverted U-shaped relationship was found between ownership concentration and market performance in both family and non-family firms, pointing out an entrenchment effect or excessive risk aversion of the controlling group. This effect is worsened for family firms. The presence of family members as CEOs, Chairmen and Board Members is also negative for a firm’s performance and family ownership was found to increase the leverage of a firm.